Motivation to move fast, motivation to wait and see: The association of prevention and promotion focus with clinicians' implementation of the JNC‐7 hypertension treatment guidelines. Issue 9 (10th August 2021) - Sanders, Mechelle; Fiscella, Kevin; Hill, Elaine; Ogedegbe, Olugbenga; Cassells, Andrea; Tobin, Jonathan N.; Williams, Stephen; Veazie, Peter
Abstract: Roughly half of the adults in the United States are diagnosed with hypertension (HTN). Unfortunately, less than one‐third have their condition under control. Clinicians generally have positive regard for the use of HTN guidelines to achieve HTN treatment goals; however, actual uptake remains low. Factors underpinning clinician variation in practice are poorly understood. To understand the relationship between clinicians' personal motivation to complete goals and their uptake of the Joint National Commission's HTN guidelines. The authors used Regulatory Focus Theory (RFT, ie, prevention and promotion focus), an empirically supported motivational theory, as a guiding framework to examine the relationship. The authors hypothesized that clinicians with high prevention focus would report following guidelines more often and have shorter follow‐up visit intervals for patients with uncontrolled blood pressure. Clinicians ( n   = 27) caring for adult patients diagnosed with HTN ( n  = 8605) in Federally Qualified Health Centers ( n  = 8). Clinicians' prevention and promotion focus scores and the number of days between visits for their patients with uncontrolled systolic blood pressure (SBP) (≥ 140 mm Hg). Consistent with RFT, 60% of prevention focused clinicians reported they always followed the monthly visit guideline for the patients with uncontrolled blood pressure, compared with 38% of promotion focused clinicians ( p  = .254). The unadjusted probability of returning for a follow‐up visit within 30 days was greater among patients whose clinician was higher in prevention focus ( p  = .009), but there was no evidence at the 0.05 significance level in our adjusted model. These findings provide some limited evidence that RFT is a useful framework to understand clinician adherence to HTN treatment guidelines.